1990
DOI: 10.1055/s-2007-1014480
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psychotropic Medication in Childhood and Adolescence in the Federal Republic of Germany

Abstract: The use of psychotropic drugs in childhood and adolescence has been the subject of intense debate during the last few years. Allegations about the excessive consumption and overprescription of these substances in younger age groups play an important role in the public discussion. In this situation it would be useful to present relevant data on the prescription volume of psychotropic drugs in childhood and adolescence. The present investigation comprises data of 1985 using the GKV drug index and the IMS prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Ausgelöst wurden die Steigerungen in den letzten eineinhalb Jahrzehnten vermutlich durch den begründeten Verdacht, dass in Deutschland bei der Indikation Aufmerksamkeitsdefizit-Hyperaktivitätsstörung (ADHS) Psychostimulanzien lange Zeit unterverordnet wurden (Elliger et al 1990). B. Ritalin) hat 2009 nur wenig zugenommen (Abbildung 39.5, Tabelle 39.11).…”
Section: Psychostimulanzienunclassified
“…Ausgelöst wurden die Steigerungen in den letzten eineinhalb Jahrzehnten vermutlich durch den begründeten Verdacht, dass in Deutschland bei der Indikation Aufmerksamkeitsdefizit-Hyperaktivitätsstörung (ADHS) Psychostimulanzien lange Zeit unterverordnet wurden (Elliger et al 1990). B. Ritalin) hat 2009 nur wenig zugenommen (Abbildung 39.5, Tabelle 39.11).…”
Section: Psychostimulanzienunclassified
“…A second factor that limits stimulant treatment outside of North America is the tight legal restrictions that are applied to stimulant prescriptions in many countries [Safer and Krager, 1984;Simeon et al, 1995]. A third factor is the frequent use of phytopharmaceuticals and homeopathic medicine in Germany [Ellinger et al, 1990] and the preferential use of hypnotics and neuroleptics for problematic youths in Germany [Minde, 1998]. …”
Section: International Perspectives On Treatment For Adhdmentioning
confidence: 99%
“…The review would be useful to practitioners and researchers who utilize psychotropic medicines with paediatric populations. The use of psychotropic medicines with children and adolescents is on the increase (Adams, 1991;Bramble & Dunkey, 1992;Kaplan, Simms, & Busner, 1994), regardless of the need for information on their appropriateness or effectiveness (Ellinger, Trott, & Nissen, 1990;Kaplan, Simms, & Busner, 1994). For instance, Bramble and Dunkey reported that 85% of235 British child and adolescent psychiatrists prescribed psychotropic drugs, whereas one in five of children receiving treatment from child psychiatrists in two US jurisdictions were prescribed psychotropic medicines.…”
mentioning
confidence: 99%